2020
DOI: 10.1002/ange.202003119
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Generation of 9‐Boratriptycene by Lewis Adduct Dissociation: Accessing a Non‐Planar Triarylborane

Abstract: A highly bent triarylborane, 9‐boratriptycene, was generated in solution by selective protodeboronation of the corresponding tetra‐aryl boron ate complex with the strong Brønsted acid HNTf2. The iptycene core confers enhanced Lewis acidity to 9‐boratriptycene, making it unique in terms of structure and reactivity. We studied the stereoelectronic properties of 9‐boratriptycene by quantifying its association with small N‐ and O‐centered Lewis bases, as well as with sterically hindered phosphines. The resultant L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 59 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Indeed, the B−P bond length in 7c• PT is comparable to that in a 9-boratriptycene•PPh 3 adduct [1.976(4) Å]. 38 A UV−vis titration experiment provided further insight into the associative behavior of 7 and PT (Figure S10). Upon addition of PT to a toluene solution of 7a, the absorption band associated with 7a at 506 nm gradually diminished, and a new absorption band at 415 nm emerged with isosbestic points at 364 and 430 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Indeed, the B−P bond length in 7c• PT is comparable to that in a 9-boratriptycene•PPh 3 adduct [1.976(4) Å]. 38 A UV−vis titration experiment provided further insight into the associative behavior of 7 and PT (Figure S10). Upon addition of PT to a toluene solution of 7a, the absorption band associated with 7a at 506 nm gradually diminished, and a new absorption band at 415 nm emerged with isosbestic points at 364 and 430 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…3 5 It has been reported that, by preventing p-π conjugation while lowering the reorganization energy with a pre-pyramidalized boron compound, the Lewis acidity of perfluorinated triarylboranes can be reached without the introduction of electron-withdrawing substituents. 6a Using the 9-boratriptycene 1 as reference, we demonstrated that switching from carbon to a cationic phosphorous bridgehead triptycene scaffold 2 leads to a dramatic increase in Lewis acidity, approaching and even surpassing triarylsilylium species. 6b Very recently, we reported the generation of the transient sulfonium-bridged analogue 3 of the 9-boratriptycene 1 and, for the first time, the high reactivity of such peculiar species in several challenging chemical transformations (Figure 1 ).…”
Section: Table 1 Pyramidalization Angle Derived From Qu...mentioning
confidence: 91%
“…Whereas the boron atom in the precursor boron ate‐complex 8 resonates at −8.7 ppm in the 11 B NMR spectrum (CDCl 3 ), the neutral boron atom in the collidine Lewis adduct 11 a gives a signal at −1.5 ppm, and that in the pyridine Lewis adduct 11b gives a signal at −1.3 ppm, in a typical range for other N−B Lewis adducts of 9‐boratriptycene ( e. g . in pyridine‐9‐boratriptycene Lewis adduct 7 with a chemical shift of δ=−1.6 ppm in 11 B NMR in CD 2 Cl 2 ) [11] . The 11 B NMR spectrum of 11 a also featured a typical sharp signal at −17.6 ppm for the tetravalent boron atom in the anion [B(C 6 F 5 ) 4 ] ‐ .…”
Section: Methodsmentioning
confidence: 99%